Spider poisoning: a report of six cases from the Central Anatolian region, Turkey - Akyildiz, Başak; Kurtoğlu, Selim; Poyrazoğlu, Hakan; Ozcan, Ahmet (The Turkish Journal of Pediatrics, 2009)
Spiders exist in every place and ecosystem. Spiders in tropical regions are particularly poisonous and can be dangerous to humans. Nearly 20,000 spider species are known, and almost all are venomous, although only 60 species worldwide are poisonous in humans. In our area, eight species are reported as poisonous in humans. Although most cases of spider bite are benign and require no intervention, severe local and systemic reactions may occur sometimes in the pediatric population, resulting in admission to the pediatric intensive care unit. In this report, we present the cases of six children from the Central Anatolian region in Turkey who were seriously affected by spider bites, and we review the literature on spider envenomation.